Analysis of movement pattern among referee in 2012 Malaysian Cup - Adnan, R.; Muzayin, N.; Sulaiman, N. (Journal of Human Sport & Exercise, 2013)
The aim of this study is to determine the contributing factors of the movement patterns toward the total distance covered by the football referees during the Malaysia Soccer Cup 2012. Seven (7) of referees who officiated the 2012 Malaysian Cup matches were been chosen into this study. All seven matches from the tournament were recorded using Astro beyond decoder and were coding with SportCode Elite Software on the selected performance indicators (P.I) as main movement patterns variables. This movement patterns were categorized as forward walking, forward jogging, forward running, standing, backward walking, backward running and sidestep running. The results analyze the frequency and the total time from the executed movement patterns for correlation and regression analysis by using the Pearson correlation and linear regression test respectively. The Pearson correlation test have shown that there is significant correlation between three movement patterns and the total distance covered by the referees which are sidestep(r= 0.97, p=0.000, p<0.01), forward walking (r= 0.930, p=0.002, p<0.01), and forward running (r= 0.807, p=0.028, p<0.05). The linear regression test have shown a positive correlation between contributing factors of the movement patterns towards the total distance covered by the football referees where the total distance covered result is 132.161 + 2.012 (sidestep) - 4.575 (forward walking) + 0.570 (forward jogging) - 2.940 (forward running) + 1.404 (backward walking) + 3.328 (backward running). Hence, this study found that movement patterns that performed by referees are contributed towards the total distance covered by football referees during a match. Thus, this study can give added values to Football Association of Malaysia (FAM), to consider the three significant movement patterns in designing physical fitness criteria for the referees).